2023
DOI: 10.5755/j01.ee.34.2.30643
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Bibliometric Analysis of Big Data in Entrepreneurship Research

Abstract: Big data technology has been widely used in entrepreneurial research in recent years. To explore the development trend and fundamental characteristics of big data in entrepreneurship (BDIE) research, we conduct a comprehensive bibliometric analysis of BDIE based on 541 publications between 1993 and 2020 from Web of Science. On the one hand, this paper focuses on some essential characteristics of the BDIE publications, such as categories, citation, H-index, and the most cited publications. On the other hand, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Some research concluded that the rapid development of digitalization has improved the environmental quality by reducing CO2 emissions, while other found that increased use of digital gadgets has worsened the environment. Additionally, the literature now available demonstrates the diverse effects of digitalization on CO2 emissions in both developing and industrialized nations, (Al-Mulali et al, 2015;Higon et al, 2017;Rahi, 2022;Sogaxa & Simpeh, 2022;Sriyakul & Chankoson, 2022;Xiao et al, 2023;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Some research concluded that the rapid development of digitalization has improved the environmental quality by reducing CO2 emissions, while other found that increased use of digital gadgets has worsened the environment. Additionally, the literature now available demonstrates the diverse effects of digitalization on CO2 emissions in both developing and industrialized nations, (Al-Mulali et al, 2015;Higon et al, 2017;Rahi, 2022;Sogaxa & Simpeh, 2022;Sriyakul & Chankoson, 2022;Xiao et al, 2023;Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%